Decline in enjoyment of physical education among culturally and linguistically diverse youth. (1st January 2013) - Dudley, Dean A.; Okely, Anthony D.; Pearson, Philip; Caputi, Peter; Cotton, Wayne G.
Enjoyment of physical education (PE) is frequently cited as a legitimate outcome in many PE curricula in Organisation for Economic Co-operation and Development (OECD) nations (Dudley et al., 2011). The purpose of this study was to examine how student enjoyment of PE changed during the first two years of secondary schooling in Australia. Participants were 586 students enrolled in six culturally and linguistically diverse (CALD) secondary schools (2 x co-educational, 2 x all girls' and 2 x all boys'). A prospective cohort design was used with data collected using the Physical Activity Enjoyment Scale (PE version) (PACES PE). There was a small ( MD = –1.8, d = –0.30) but significant ( p < .001) decline in overall enjoyment of PE between Grade 7 and Grade 8. The decline in enjoyment of PE was greatest among girls (regardless of school-type) and having to change uniforms had the largest negative effect ( d = –0.42) of that decline. Peer relationships had the largest negative effect ( d = –0.40) on boys enjoyment of PE. It is recommended that schools examine PE uniform policies and increasing teacher and peer support strategies in PE to maintain enjoyment during middle/high school.